Precision Medicine in Adult Obstructive Sleep Apnea and Home Diagnostic Testing: Caution in Interpretation of Home Studies Without Clinician Input Is Necessary - Do, Timothy Quy-Phong; MacKay, Stuart Grayson; Lam, Matthew Eugene; Sideris, Anders William; Jones, Andrew Christopher; Chan, Lyndon Sidney (Frontiers in Neurology, 2022)
Purpose: To assess the validity of home sleep apnoea test directed diagnosis and treatment of obstructive sleep apnoea (OSA) in a real-life clinical setting and establish the extent to which clinical evaluation alters diagnosis and therapeutic intervention, in the context of the evolving realm of precision medicine. Methods: Retrospective consecutive cohort study of 505 patients referred to a single center between 15th September 2015 to 14th September 2016, multidisciplinary specialist sleep clinic presenting with a home sleep apnoea test prior to referral. We evaluated the effect of sleep medicine practitioner (SMP) and ear, nose and throat surgeon (ENTS) review on patient diagnoses, disease severity and management options in OSA. Results: 115 patients were included. Repeat evaluation with in-lab polysomnogram (PSG) was required in 46/115 (40.0%) of patients, of which 20/46 (43.5%) had OSA severity changed. SMP review decreased the need for repeat testing with formal in-lab PSG (p < 0.05) and increased patient acceptance of continuous positive airway pressure as a long-term management option for OSA. SMP/ENTS review resulted in discovery of a non-OSA related sleep disorder or change in OSA severity in 47.8% (55/115). ENTS review resulted in additional or changed diagnosis in 75.7% (87/115) of patients. Conclusion: In the clinical assessment and diagnosis of OSA, patients should be reviewed by medical practitioners with an interest in sleep disorders to better navigate the complexities of assessment, as well as the identification of co-morbid conditions.